2009
DOI: 10.1007/s00335-009-9182-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of maternal QTL affecting growth and obesity in adult mice

Abstract: Most quantitative trait loci (QTL) studies fail to account for the effect that the maternal genotype may have on an individual's phenotypes, even though maternal effect QTL have been shown to account for considerable variation in growth and obesity traits in mouse models. Moreover, the fetal programming theory suggests that maternal effects influence an offspring's adult fitness, although the genetic nature of fetal programming remains unclear. Within this context, our study focused on mapping genomic regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 53 publications
3
24
2
Order By: Relevance
“…We identified maternal-effect QTL on both of the chromosomes (2 and 7) examined in the study by Casellas et al (2009) (see above), although the locations of the chromosome 7 QTL are relatively far apart. The chromosome 2 QTL are in overlapping regions, but the locus identified by Casellas et al (2009) has effects on late adult traits, while meQTL2.2 has effects limited to earlier life, although it is important to note that Casselas et al did not examine newborn or juvenile weights.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…We identified maternal-effect QTL on both of the chromosomes (2 and 7) examined in the study by Casellas et al (2009) (see above), although the locations of the chromosome 7 QTL are relatively far apart. The chromosome 2 QTL are in overlapping regions, but the locus identified by Casellas et al (2009) has effects on late adult traits, while meQTL2.2 has effects limited to earlier life, although it is important to note that Casselas et al did not examine newborn or juvenile weights.…”
Section: Discussionmentioning
confidence: 95%
“…These studies have shown that they are often one of the largest components of variation for traits expressed early in life, with effects generally eroding after weaning (see Wilson and Festa-Bianchet 2009 for a review of persistence), but often persisting at a low level into adulthood (e.g., Riska et al 1984Riska et al , 1985Cowley et al 1989;Jarvis et al 2005;Casellas et al 2009). It is important to keep in mind that most of our understanding of maternal effects has come from studies that used approaches that cannot differentiate between genetic-and environmentally based maternal effects (but exceptions exist; e.g., Wilson …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations